29PA retrospective analysis of 66 colorectal cancer cases from Guy's and St Thomas' (GSTT) Molecular Tumour Board. (7th November 2019) - Kapiris, M; Josephs, D; Kulkarni, A; Valganon, M; De Souza, B; Campbell, J; Churm, F; Nickless, G; Ross, P; De Naurois, J; Maisey, N; Thillai, K; et al.
Abstract: Background: The utility of next generation sequencing (NGS) is rapidly evolving within our medical practice with various applications. The 100K Genomes Project was established to sequence 100 000 genomes from NHS patients with cancer or rare diseases, and to date actionable findings have been found for approximately 50% of cancer cases. Data from the 100K Genomes Project were reviewed at Guy's Hospital Molecular Tumour Board (MTB). Methods: Whole genome sequencing (WGS) was performed for the 100K Genomes Project and Genomics England using an Illumina platform. Results: Between December 2016 and August 2018, 66 patients with colorectal cancer (CRC) were treated with surgery at GSTT. Median age was 68.5 (52-95). Majority were left sided (69%) vs right sided (30%) adenocarcinomas. TNM status was 1.5% / 47% / 37.9% / 13.6% for stage I/II/III/IV respectively. Analyses were performed in FFPE (35.8%) and frozen tissue (64.2%). Median estimated tumour purity was 53.5% (20-100%). Median tumour mutational burden (TMB) was 5.92 (2.94-173.26). Mutational signatures 6, 10 and 15 were found for 8 patients and were associated with high TMB. A total of 557 Domain 1 (actionable) variants (range 1-68) were identified for this cohort. After review in the MTB, at least one clinically relevant actionable variant was identified for 59.7% of the patients; KRAS 37.3%, NRAS 6%, BRAF 11.9%, TP53 70.1%, PIK3CA 35.8%, ATM 17.9%, RICTOR 14.9%, APC and PTEN 11.9% each and mTOR 8.6%. Somatic BRCA1 and BRCA2 variants were found in 7.6% and 12.1% respectively. Further validation was recommended for 9 patients (13.4%). DPYD alterations were identified in 11.9%, but none of the clinically relevant DPYD mutations related to 5FU toxicity were discovered for 2 of the patients that were tested. 9.4% were identified with potentially pathogenic germline variants (7.6% with RAD51D, RAD51C, MUTYH, MSH6 and PMS2 class 4 & 5 variants) and referral to Clinical Genetics was recommended. Conclusions: GSTT MTB identified actionable mutations in more than half patients in the CRC cohort, out of whom 14% had alterations that made them eligible for clinical trials. Over 9% had potentially pathogenic germline variants. Our data from this small cohort resemble data in the literature from other MTBs. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.